Essential Oil Composition of Centaurea stenolepis Kerner. from Turkey - Polatoglu, Kaan; Sen, Ali; Bulut, Gizem; Bitis, Leyla; Goren, Nezhun (TAYLOR & FRANCIS LTD, 2014)
Essential oil composition of Centaurea stenolepis Kerner flowers and stems were investigated with GC, GC-MS. Flowers and stems of C. stenolepis had very low essential oil yield <0.01 % (v/w). Twenty eight compounds were identified in the flower oil which represent 53.5 % of the oil. Main components of the flower oil include caryophyllene oxide 12.6 %, hexadecanoic acid 10.6 % and beta-Eudesmol 7.2 %. Forty compounds were identified in the stem oils which represent 74.2 % of the oil. Main components of the stem oils include hexadecanoic acid 38.4 % and phytol 12.9 %. Both flower and stem oils were rich on oxygenated sesquiterpene hydrocarbons and fatty acids.
Keywords: Phytol; Essential Oil; beta-Eudesmol; Caryophyllene oxide; Hexadecanoic acid; Asteraceae; Centaurea; PSEUDOSCABIOSA SUBSP PSEUDOSCABIOSA; ASTERACEAE GROWING WILD; VOLATILE COMPONENTS; CHEMICAL-COMPOSITION; ANTIMICROBIAL ACTIVITY; SCHULTZ BIP.; AERIAL PARTS; SESQUITERPENE LACTONES; ANTIBACTERIAL ACTIVITY; CHILIOPHYLLUM FISCH; Plant Sciences